Answer:
In mathematics, exponential decay describes the process of reducing an amount by a consistent percentage rate over a period of time. ... You can compare and contrast the differences between exponential growth and decay, but it's pretty straightforward: one increases the original amount and the other decreases it.
The equation (5X-15=-75 is equal to B D and E because they all have -75 at they end of them!
Answer:
1) (2x + 2)(x + 2)
2) 2(x + 1)(x - 1)
3) (x^2 + 3)(x^2 - 3)
4) 2x(x + 5)(x - 2)
5) (5x + 2y)(5x - 2y)
Step-by-step explanation:
1)
2x^2 + 6x + 4
= 2x^2 + 4x + 2x + 4
= 2x(x + 2) + 2(x + 2)
= (2x + 2)(x + 2)
2)
2x^2 - 2
= 2(x^ 2 - 1) (The difference of two squares)
= 2(x + 1)(x - 1)
3)
x^4 - 9 (The difference of two squares)
=(x^2 + 3)(x^2 - 3)
4)
2x^3 + 6x^2 - 20x
= 2x(x^2 + 3x - 10)
= 2x(x + 5)(x - 2)
5)
25x^2 - 4y^2 (The difference of two squares)
= (5x + 2y)(5x - 2y)
I’m pretty sure answer is A and i’m
(a). How much the T-shirt cost.
(b). 23=12+x
(c). 23-12=x; x= 11
(d) the T-shirt cost $11.